Exploring the Relationship between Customer Engagement and Brand Advocacy among TikTok Shop Consumers: A Qualitative Literature Review - Angmalisang, Stefani I.; Angmalisang, Harrychoon; Rattu, Syaloomitha G.; Setlight, Praished M.; Pakasi, Vianti R.; Muaja, Reginaseli M.; Sembiring, Otniel S.; Pangemanan, Enrique; Dugupa, Simon; Sumolang, Gabriel (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to explore the relationship between customer engagement and brand advocacy from the perspective of consumers on TikTok Shop. The research focuses on how consumers' interactions with brands affect their willingness to be brand advocates. A descriptive qualitative approach is used with literature review as the main method. Data was collected through a systematic review of journals related to customer engagement, brand advocacy, and digital marketing on TikTok Shop. Thematic analysis is used to identify patterns of relationships between variables. Results show that customer engagement has a significant impact on brand advocacy. Engagement is formed from creative content, interactive communication, and digital community participation. Consumers who are emotionally and socially connected are more likely to share positive experiences and become brand advocates. This study provides new insights by highlighting the dynamics of brand engagement and advocacy on video-based platforms like TikTok Shop, emphasizing the importance of emotional engagement and community building as a digital marketing strategy.